Proceedings of the 13th EAI International Conference on Performance Evaluation Methodologies and Tools 2020
DOI: 10.1145/3388831.3388840
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Explicit Control Policies for Markov Decision Processes Using Symbolic Regression

Abstract: In this paper, we introduce a novel approach to optimizing the control of systems that can be modeled as Markov decision processes (MDPs) with a threshold-based optimal policy. Our method is based on a specific type of genetic program known as symbolic regression (SR). We present how the performance of this program can be greatly improved by taking into account the corresponding MDP framework in which we apply it.The proposed method has two main advantages: (1) it results in near-optimal decision policies, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The proposed SR-based approach is still in its infancy, but initial results are promising. In [4], it was shown that the approach can be used to obtain symbolic expressions for MDP value functions, and [2] gives an example where the approach is also useful to approximate optimal control policies in MDPs.…”
Section: Remarkmentioning
confidence: 99%
“…The proposed SR-based approach is still in its infancy, but initial results are promising. In [4], it was shown that the approach can be used to obtain symbolic expressions for MDP value functions, and [2] gives an example where the approach is also useful to approximate optimal control policies in MDPs.…”
Section: Remarkmentioning
confidence: 99%
“…In this article Hristov, Bhulai, van der Mei, and Bosman () (cf also Hristov, ), optimal threshold approximations for the M/M/1 queue with admission control have been derived using an evolutionary algorithm, called symbolic regression. Typically, rejection cost truecr=1 is used.…”
Section: M/m/1 Queue With Admission Control: Construction Of VI Initimentioning
confidence: 99%